2015
DOI: 10.3168/jds.2014-8335
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manual and mechanical stimulation on oxytocin release and milking characteristics in Holstein cows milked 3 times daily

Abstract: Prestimulation administered to a cow before attachment of the milking unit has historically been performed manually. Development of innovative milking technology has allowed manual stimulation to be replaced by mechanical forms of stimulation. Holstein cows (n=30) were enrolled in a crossover design to determine the effect of manual stimulation (forestripping and drying) and high-vibration pulsation on oxytocin profiles, milk yield, milk flow rates, incidence of delayed milk ejection causing bimodal milk flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 16 publications
3
26
1
Order By: Relevance
“…Data from electronic on-farm milk meters that routinely measure milking characteristics have been established as measures of parlor performance (Reid and Stewart, 2007;Treichler and Reid, 2013), premilking udder preparation (Watters et al, 2012(Watters et al, , 2015, and assessment of liner performance . In addition, recent case-control studies have investigated the association of milking characteristics with the risk of clinical mastitis (Guarín and Ruegg, 2016;Penry et al, 2017a).…”
Section: Short Communicationmentioning
confidence: 99%
“…Data from electronic on-farm milk meters that routinely measure milking characteristics have been established as measures of parlor performance (Reid and Stewart, 2007;Treichler and Reid, 2013), premilking udder preparation (Watters et al, 2012(Watters et al, , 2015, and assessment of liner performance . In addition, recent case-control studies have investigated the association of milking characteristics with the risk of clinical mastitis (Guarín and Ruegg, 2016;Penry et al, 2017a).…”
Section: Short Communicationmentioning
confidence: 99%
“…The p53 is a stress-induced transcription factor that controls various cellular response mechanisms including cell cycle arrest and apoptosis (Li and Jogl, 2009). Its expression can influence the release of oxytocin response during pregnancy and lactation in model organisms (Soloff and Wieder, 1983) and oxytocin is released in cows for the letdown of milk (Watters et al, 2015). The timing of oxytocin release relative to milk removal is an important factor affecting milk ejection and persistency during lactation (Nostrand et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…3a with injection starting at 30 s and electrophoresis starting at two minutes and 30 s. It should be observed that as the sample approaches the UV LED for measurement at approximately 18 min, there is no discernable response, indicating the ciprofloxacin is not present. It should be noted that through careful selection of voltages and channel lengths www.nature.com/scientificreports/ (with the electric field being approximately equal to the ratio between these values), it is envisioned that the analysis time can be greatly reduced, in accordance with dairy requirements for analysis time 37 . The microchip capillary electrophoresis dairy device is then operated with a milk sample containing 0.25 mM ciprofloxacin to establish an antibiotic-present response (being the change of the output voltage at the temporal region of interest).…”
Section: Antibiotic-absent and Antibiotic-present Operation The Micrmentioning
confidence: 99%